Analysis of Using Multi-Angle Conventional Ultrasound Scanning for Efficient 3-D Object Imaging - SABINIOK, Maciej; OPIELIŃSKI, Krzysztof J.; LIS, Sylwia (Archives of Acoustics, 2019)
The purpose of this work is to examine the possibility of using multi-angle conventional ultrasound B-mode scanning in efficient 3-D imaging. In the paper, the volume of an object is reconstructed from vertical projections registered at fixed angular positions of the multi-element linear ultrasonic probe rotated in relation to the object submerged in water. The possible configurations are: vertical lateral, vertical top or vertical bottom. In the vertical lateral configuration, the ultrasonic probe acquires 2-D images of object’s vertical cross-sections, turning around its lateral surface. In the vertical top or bottom configuration, the ultrasonic probe acquires 2-D images of the object’s vertical cross-sections, turning on the horizontal plane over the top or under the bottom surface of the object. The method of recording 3-D volume of an object’s structure and reconstruction algorithm have been designed. Studies show the method in the vertical top or bottom configuration could be successfully applied to the effective 3-D visualisation of the structure of the female breast in vivo as the new complement ultrasonic imaging modality in the prototype of the developed ultrasound tomography scanner.